Suppression of rat cytomegalovirus replication by antibodies against gamma interferon. - Haagmans, B L (1994)
The role of gamma interferon (IFN-gamma) in the resolution of rat cytomegalovirus (RCMV) infection was investigated. In the spleen, IFN-gamma-producing cells reached maximum numbers on day 7 after infection. Prophylactic treatment with high doses of recombinant rat IFN-gamma exerted antiviral activity in fibroblasts and protected immunosuppressed rats against a lethal RCMV challenge. Remarkably, in immunocompetent rats, neutralization of endogenous IFN-gamma activity significantly reduced the numbers of RCMV antigen-expressing cells in the spleen, the predominant site of viral replication. Moreover, protection of radiation-immunosuppressed infected rats by transferred immune T cells was enhanced by coinjection of IFN-gamma neutralizing antibodies. The observations were paralleled by in vitro findings: low concentrations of IFN-gamma enhanced viral replication in both macrophages and fibroblasts. These data suggest that IFN-gamma can play different and even opposite roles in the regulation of RCMV replication in vivo; T lymphocytes may contribute to the progression of RCMV infection by secreting IFN-gamma.